TRANSFORMASI SOSIAL-BUDAYA MASYARAKAT INDONESIA - Nurdien Harry Kistanto (Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
Social scientists have conceptualized several stages of sociocultural transformation as societal development. One version modified in this article constitutes a typology of preindustrial and industrial societies which consists of one, hunting & gathering societies; two, pastoral societies; three, village agrarian societies; four, advanced traditional agrarian societies; and five, industrial societies; and six, postindustrial societies. To analyse the sociocultural transformation which happens in the Indonesian society, one has to observe and consider the long historical background which produces social heterogeneity. Thus, the direction and ideals of sociocultural transformation can be identified and conceptualized.